4-(4-Fluorophenyl)-3-(pyridin-4-yl)-1-(2,4,6-trichlorophenyl)-1H-pyrazol-5-amine - Abu Thaher, Bassam (International Union of Crystallography, 2012)
In the title compound, C(20)H(12)Cl(3)FN(4), the pyrazole ring forms dihedral angles of 47.51 (9), 47.37 (9) and 74.37 (9)° with the directly attached 4-fluorophenyl, pyridine and 2,4,6-trichlorophenyl rings, respectively. Only one of the two amino H atoms is involved in hydrogen bonding. The crystal packing is characterized by N—H⋯N hydrogen bonds, which result in infinite chains parallel to the c axis.